A multivariate analysis of the impact of knowledge and relationships on perceptions about aging among generation Z—a starting point for public health strategies - Silvia Puiu; Mihaela Tinca Udriștioiu; Mihaela Zăvăleanu (Frontiers in Public Health)
IntroductionThe main objective of the study is to better understand how knowledge about the natural process of aging and its implications, as well as the relationships with old people, shapes the perceptions of generation Z toward the meaning of old age.MethodsThe research methodology we used is partial least squares structural equation modeling in which we developed a model with five variables: thoughts about aging, feelings about aging, healthy habits, knowledge about aging and relationship with old people.ResultsThe results revealed the direct and positive impact of both knowledge and relationships on the thoughts and beliefs of generation Z.DiscussionThe findings are useful for managers in the public sector responsible for shaping more efficient health strategies meant to normalize aging and prepare young individuals for healthy aging.